Santo Domingo de Guzmán and his Vision of the Study - Condori Cutimbo, Claudio Raúl (2018)
This paper reflects on the work of Saint Domingo de Guzmán, in particular the importance of study as a means for evangelization and the presentation of Truth, which is Jesus Christ himself. It aims to rescue some elements of the meaning of study for the Order of Preachers. To this end, it will be essential to know the context in which Saint Domingo de Guzmán is situated as well as the characteristics of his vision of study. Finally, it is important to know the contributions made, even to this day, by the Order of Preachers, to the culture and development of science and research in Peru by means of the establishment of numerous colleges and universities.